The effects that secondary parkinsonian syndromes have on health status - Dawid Kościołek; Michał Urbaś; Jakub Misiak; Aleksandra Kościołek; Martyna Kępczyk; Oliwia Czekaj; Miłosz Ojdana; Kaja Surowiecka; Oliwia Kwaśniewska; Yehor Demianenko (Kazimierz Wielki University, 2024)
Introduction and aim of work: The parkinsonian syndrome is a component of Parkinson's disease. A thorough neurological examination can detect symptoms belonging to the parkinsonian syndrome. Diagnosis using the Queen Square Brain Bank criteria is based on the presence of bradykinesia along with one additional symptom in the patient. These include muscle rigidity or resting tremors at a frequency of 4-6 Hz, or postural disturbances that cannot be explained by visual, vestibular, cerebellar, or deep sensory disorders. The parkinsonian syndrome can occur in idiopathic Parkinson's disease, hereditary disorders, secondary parkinsonism, or be part of an atypical parkinsonian syndrome. The aim of the study was to discuss the diagnostic features and differences in the occurrence of the parkinsonian syndrome as a component of Parkinson's disease, both within the context of other neurological disorders. Materials and methods: The foundation of the research was medical articles gathered from the Google Scholar database. The studies were conducted by analyzing keywords such as "parkinsonism," "drug-induced parkinsonism," and "vascular parkinsonism." Results: Secondary parkinsonism, or secondary parkinsonism syndrome, can be indicated by clinical features such as: disease onset below the age of 40, abrupt onset, rapid disease progression, symptoms related to medication use, and symptoms associated with the underlying condition. In addition to clinical evaluation, imaging studies are also employed. Various conditions can lead to the development of secondary parkinsonism, including hydrocephalus, brain tumors, encephalitis, cerebral atherosclerosis, traumatic brain injuries, medications, and poisoning. The aforementioned conditions exert different mechanisms of influence on the central nervous system.